Niosomes: Prepration, Evaluation & Applications - Kandpal, Ramesh; Teotia, Deepak (Journal of Neonatal Surgery, 2025)
Researchers are now more interested in nanocarrier technology because it has many safety and effectiveness benefits, such as more fully therapeutic delivery with a range of pharmacological effects, better targeting capabilities, and fewer negative reactions than other carrier systems. Niosomes also showed promise as a new and innovative medication administration system. A vesicular drug carrier method that offers targeted and regulated drug delivery is niosomes. It can be unilamellar, oligolamellar, or multilamellar and contains charged molecules, cholesterol or its derivatives, & non-ionic surfactants. The essential knowledge about niosomes, including their structure, types, perks and drawbacks, administration routes, preparation techniques, factors influencing their formation, evaluation criteria for niosomes, applications, and currently available commercial formulations, is illustrated in this review article